2017
DOI: 10.1142/s2010135x17500126
|View full text |Cite
|
Sign up to set email alerts
|

A novel sol–gel route to synthesize (Sr0.5Ba0.5)Nb2O6 ceramics with enhanced electrocaloric effect

Abstract: (Sr 0:5 Ba 0:5 )Nb 2 O 6 ultra-fine powders were synthesized by a novel sol-gel route, and the mechanism of the reaction was discussed. SrCO 3 , BaCO 3 , oxalate niobium and citric acid were used to initiate the sol-gel process, and ethylene glycol (EG) was added to further polymerize the cross-linking structure. The evolution of the (Sr 0:5 Ba 0:5 )Nb 2 O 6 phase, the reaction process and the microstructures were investigated by X-ray diffraction (XRD), Raman spectroscopy, Fourier transform infrared spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 31 publications
(27 reference statements)
1
9
0
Order By: Relevance
“…The formation of Sr 0.5 Ba 0.5 Nb 2 O 6 together with an amorphous fraction at low temperature can often be seen using wet-chemical methods [21,30,32,39]. Recently, Chen et al [19] prepared Sr 0.5 Ba 0.5 Nb 2 O 6 by a sol-gel synthesis using 1,2-ethanediol and citric acid as polymerization agents. Calcination of that gel resulted in considerable amounts of secondary phases up to 1100 °C.…”
Section: Synthesis and Powder Characterizationmentioning
confidence: 99%
“…The formation of Sr 0.5 Ba 0.5 Nb 2 O 6 together with an amorphous fraction at low temperature can often be seen using wet-chemical methods [21,30,32,39]. Recently, Chen et al [19] prepared Sr 0.5 Ba 0.5 Nb 2 O 6 by a sol-gel synthesis using 1,2-ethanediol and citric acid as polymerization agents. Calcination of that gel resulted in considerable amounts of secondary phases up to 1100 °C.…”
Section: Synthesis and Powder Characterizationmentioning
confidence: 99%
“…[2,3] Aurivillius phases with relaxor-like diffused behavior are popular for medium and large-scale refrigeration. [4] Quian et al and Goupil et al reported the ECE enhancement near the critical point, morphotropic phase boundary, respectively, in bulk ceramics due to the presence of a mix of polar phases of nanoregions with different symmetries. [5,6] Large entropic changes occur near phase transitions like ferroelectric to paraelectric, antiferroelectric to ferroelectric, and even in ferroelectric to ferroelectric; compositional modifications are known crucial to the nature of phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, operating temperature range T span (the range of temperature over which ΔT stays 0.9 times ΔT peak ) for achieving maximum ECE change at comparatively low electric fields is also desirable. [4,5] Recently published work by Chen et al and Hamad in an isolated manner on strontium bismuth niobate (SBN) bulk and thin films reiterated the inclination of researchers to stimulate ECE in Sr-based bismuth-layer structured ferroelectrics (BLSF) family members for augmented solid-state refrigeration. [4,9] An assisting study by Axelsson et al on the effects of relaxor characteristics and diffused phase transition on ECE strength in strontium bismuth niobate tantalate (SBNT) compounds proved to be very useful.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations